HER+: Harnessing Gender and Social Equality for Resilience in Agrifood Systems - Haan, Nicoline C. de; Gilligan, Daniel O.; Cole, Steven M.; Roy, Shalini; Kosec, Katrina; Nchanji, Eileen Bogweh; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2022)
Gender inequalities remain deeply entrenched, limiting the potential of women—especially those from agriculture-dependent communities—to be empowered and to build social, economic and technological resilience to climate change.